Evaluation Of Existing ICT Infrastructure In KUIM - Nurdiana Azizan; Najwa Hayaati Mohd Alwi; Shaharudin Ismail; Kamaruzzaman Seman (Universiti Sains Islam Malaysia, 2024)
Information and Communication Technology (ICT) has been created to fasten and easier the human tasks. Nowadays, the ICT is becoming more widely used by academic institutions to support the academic activities particularly in teaching and research. Kolej Universiti Islam Malaysia (KUIM) is being established to uphold and enhance Islamic Studies in education with the usage of information and communication technology (ICT) in its academic activities. KUIM provides the ICT infrastructure to the staffs to effectively integrate the facilities in performing their job tasks. The evaluation of the existing ICT infrastructure at KUIM is in need to identify the strength and availability of the facilities. Therefore this research highlights the ICT infrastructures available at KUIM in terms of hardware, software, services and maintenance. The other aspect this research will look will be the users' satisfaction towards the availability and performance of the infrastructure. At the end of this study, we identified the existing computer hardware, software used in KUIM. This is including the whereabouts and specifications details of those items. Secondly, this research understood the process of administration of the ICT infrastructure. This includes the performance, services, network and security management. Finally, this study recognized the satisfaction and IT literacy among the staffs. The evaluation of current ICT infrastructure is in need so that it can benefit the user and organization as a whole. The user can take full advantage of the available facilities in order to provide the best performance and the organization can plan for future ICT uses for the development purposes. The outcome of this research is expected to provide the information needed for the growth of the university.